Inter‐Relations Between Ethnic‐Racial Discrimination and Ethnic‐Racial Identity Among Early Adolescents. Issue 1 (11th August 2020) - Del Toro, Juan; Hughes, Diane; Way, Niobe
Abstract : The authors examined whether the longitudinal inter‐relations between ethnic‐racial discrimination and ethnic‐racial identity vary according to the perpetrator of discrimination. The authors used three waves of data from early adolescents ( n  = 387; ages 11–12 at Wave 1) to assess the strength and direction of relations between perceived discrimination from non‐school adults and peers vis‐à‐vis ethnic‐racial identity exploration, commitment, private regard, and public regard. Cross‐lagged autoregressive path analyses showed that more frequent discrimination, regardless of source, had reciprocal and significant longitudinal inter‐relations with exploration and public regard. Peer discrimination predicted lower commitment and private regard 1 year later, whereas non‐school adult discrimination did not. Implications are discussed in relation to the role of peers and ethnic‐racial identity processes.